2018
DOI: 10.1186/s13195-017-0329-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion kurtosis imaging allows the early detection and longitudinal follow-up of amyloid-β-induced pathology

Abstract: Background: Alzheimer's disease (AD) is a progressive neurodegenerative disorder and the most common cause of dementia in the elderly population. In this study, we used the APP/PS1 transgenic mouse model to explore the feasibility of using diffusion kurtosis imaging (DKI) as a tool for the early detection of microstructural changes in the brain due to amyloid-β (Aβ) plaque deposition. Methods: We longitudinally acquired DKI data of wild-type (WT) and APP/PS1 mice at 2, 4, 6 and 8 months of age, after which the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(94 citation statements)
references
References 54 publications
5
86
2
Order By: Relevance
“…Previous dMRI studies have reported similar trends of decrease in diffusivity and increase in kurtosis in the brain using different mouse models of AD [35,36,45,46]. Our diffusion tensor (DT) metrics results are in general concordance with Sun et al [45], where reduced D ⊥ with age in the EC of the transgenic group (APPsw) is seen in the results.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Previous dMRI studies have reported similar trends of decrease in diffusivity and increase in kurtosis in the brain using different mouse models of AD [35,36,45,46]. Our diffusion tensor (DT) metrics results are in general concordance with Sun et al [45], where reduced D ⊥ with age in the EC of the transgenic group (APPsw) is seen in the results.…”
Section: Discussionsupporting
confidence: 90%
“…DKI has been used in human studies to investigate tissue microstructural changes associated with aging [22][23][24][25] and AD [26,27], particularly for assessing WM abnormalities [28][29][30][31]. Furthermore, the extra diffusional kurtosis (DK) measures have a demonstrated sensitivity to brain pathology in a variety animal models [32][33][34], including AD mouse models [35,36].…”
Section: Introductionmentioning
confidence: 99%
“…Second, a large number of sensitive baseline measures are fundamental to detect true effects of lifestyle interventions on cognitive decline and prevention of neurodegenerative diseases, and fully explain and understand the different age-related trajectories ( Nilsson and Lövdén, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, opposite changes in hippocampal MD, AD and RD was observed between 6-8 mo in the APP/PS1 mouse using a diffusion kurtosis image acquisition scheme (Praet et al, 2018).…”
Section: Discussionmentioning
confidence: 92%